2011
DOI: 10.1016/j.pestbp.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of a pyrethroid resistant African malaria vector, Anopheles funestus, from southern Africa

Abstract: Anopheles funestus is one of the major malaria vectors in southern Africa and several populations in this region are resistant to pyrethroids. The current study uses a microarray based approach to identify genes up-regulated in the pyrethroid resistant population, FUMOZ, from Mozambique. As the full set of detoxification genes in An. funestus are unknown, this study investigated the utility of the An. gambiae 'detox chip' to screen for differentially expressed detoxification genes in An. funestus. Differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Previous studies have shown that several classes of GSTs and multiple isoforms within each class can be inhibited by various pyrethroids . Microarray analysis suggests that several GST genes in pyrethroid‐resistant strains of A. gambiae , Cimex lectularius , Anopheles funestus and Spodoptera frugiperda are overexpressed . Accumulating evidence indicates that GSTs contribute to pyrethroid resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that several classes of GSTs and multiple isoforms within each class can be inhibited by various pyrethroids . Microarray analysis suggests that several GST genes in pyrethroid‐resistant strains of A. gambiae , Cimex lectularius , Anopheles funestus and Spodoptera frugiperda are overexpressed . Accumulating evidence indicates that GSTs contribute to pyrethroid resistance.…”
Section: Resultsmentioning
confidence: 99%
“…gambiae detox chip allows for the evaluation of transcription of a large number of genes simultaneously, but the criteria one uses to find significance will determine how many genes are of interest for further study. In other studies (both same- and cross-species hybridizations) the cut-off for significance in terms of fold change ranged from >1.5 to 2.0, and the p -value cut-off for significance ranged form < 0.001 to <0.05 [32,33,42-44]. Generally, where a higher fold-change was used as criteria to identify over-transcribed genes, a lower p -value cut-off was also used to determine significance, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Genes associated with pyrethroid resistance include the esterase, GST and P450 super families [8-13]. Metabolic detoxification of pyrethroids has been demonstrated in An.…”
Section: Introductionmentioning
confidence: 99%